A Further Analysis of the Lead–Lag Relationship Between the Cash Market and Stock Index Futures Market - Chan, Kalok (Review of Financial Studies, 1992)
The intraday lead–lag relation between returns of the Major Market cash index and returns of the Major Market Index futures and S&P 500 futures is investigated. Empirical results show strong evidence that the futures leads the cash index and weak evidence that the cash index leads the futures. The asymmetric lead–lag relation holds between the futures and all component stocks, including those that trade in almost every five-minute interval. Evidence indicates that when more stocks move together (market-wide information) the futures leads the cash index to a greater degree. This suggests that the futures market is the main source of market-wide information.